Use of mucolytics in COPD: A Delphi consensus study - Papi, Alberto; Avdeev, Sergey; Calverley, Peter M A; Cordeiro, Carlos R; Jesenak, Milos; Koblížek, Vladimir; Petkova, Diana; Rogliani, Paola; Tarraf, Hesham; Tzanakis, Nikolaos; Ulmeanu, Ruxandra; Uzaslan, Esra; et al. (Respiratory medicine, 2020)
BACKGROUND: International guidelines recommend mucolytic agents as add-on therapy in selected patients with COPD because they may reduce exacerbations and improve health status. As the evidence varies among mucolytic agents, we used the Delphi method to assess consensus amongst an international panel of COPD experts on mucolytics use in COPD. METHODS: 53 COPD experts from 12 countries were asked to complete an online questionnaire and rate their agreement with 15 statements using a 5-point scale. The mucolytic agents evaluated were carbocysteine, erdosteine and N-acetylcysteine (NAC). Data were collected anonymously and consensus presented using descriptive statistics. RESULTS: The 47 respondents reached consensus on the statements. They agreed that regular treatment with mucolytic agents effectively reduces the frequency of exacerbations, reduces the duration of mild-to-moderate exacerbations, and can increase the time to first exacerbation and symptom-free time in COPD patients. Consensus was consistently highest for erdosteine. The experts agreed that all three mucolytics display antioxidant and anti-inflammatory activity. Erdosteine and NAC were thought to improve the efficacy of some classes of antibacterial drugs. All three mucolytics were considered effective for the short-term treatment of symptoms of acute exacerbations when added to other drugs. The panel agreed that approved doses of mucolytic agents have favorable side-effect profiles and can be recommended for regular use in patients with a bronchitic phenotype. CONCLUSIONS: Consensus findings support the wider use of mucolytic agents as add-on therapy for COPD. However, the differences in pharmacological actions and clinical effectiveness must be considered when deciding which mucolytic to use.
Keywords: thioglykoláty; Surveys and Questionnaires; zdravotní stav; Consensus; Humans; COPD; Thiophenes; karbocystein; Female; Delphi study; Carbocysteine; internacionalita; Internationality; výsledek terapie; acetylcystein; lidé; Thioglycolates; Exacerbation; průzkumy a dotazníky; expektorancia; konsensus; Expectorants; Practice Guidelines as Topic; ženské pohlaví; Health Status; Male; Treatment Outcome; směrnice pro lékařskou praxi jako téma; chronická obstrukční plicní nemoc; Symptom Flare Up; Erdosteine; Pulmonary Disease, Chronic Obstructive; syndrom vzplanutí nemoci; thiofeny; mužské pohlaví; Acetylcysteine; kombinovaná farmakoterapie; Drug Therapy, Combination; Mucolytic